Production of kombucha tea as alternative source of probiotic drink in Mandailing sub-district Tebing Tinggi City - Candra, Andy; Fitri, Fasihah Irfanii; Nazriani, Dina; Rahayu, Siti Utari (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Kombucha is a well-known health probiotic drink. Kombucha was first used in East Asia (Manchuria) in the Tsin Dynasty around 220 BC which was used for detoxification. This probiotic drink is a fresh drink from a slightly sweet, slightly acidic tea that is consumed worldwide. Kombucha tea is obtained from tea leaf infusion by fermentation with SCOBY (symbiotic culture of yeast and bacteria). The taste of the fermented tea is like apple cider vinegar. With the development of The Kombucha era, it has been studied by many researchers and provides excellent health benefits including as a source of antioxidants to prevent free radicals, antibacterial, anticancer, for diabetes, cardiovascular (heart disease), digestive problems and low body immunity because age factor. In the Mandailing sub-district, Tebing Tinggi city, there is a lack of public awareness of health. With the training in making kombucha probiotic drink, it is hoped that residents in that area can apply this health drink to improve a healthy lifestyle.